2015
DOI: 10.1002/path.4656
|View full text |Cite
|
Sign up to set email alerts
|

Model systems of human papillomavirus‐associated disease

Abstract: Human papillomaviruses (HPVs) cause a range of serious diseases, including the vast majority of cervical cancers, most anal cancers and around half of head and neck cancers. They are also responsible for troublesome benign epithelial lesions, including genital warts and laryngeal papillomas, and in some individuals HPVs lead to recurrent respiratory papillomatosis and other difficult-to-manage diseases. As a result, there is a great need for model systems that accurately mimic papillomavirus infections in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
115
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(118 citation statements)
references
References 125 publications
(180 reference statements)
1
115
0
2
Order By: Relevance
“…These include bovine PV (BPV1 and BPV2), cotton rabbit PV (CRPV), and canine PV (COPV and CfPV2), all of which have been used for vaccine and pathogenesis studies (Campo, 2002;Buitrago-Pérez et al, 2012). In the absence of a proper mouse HPV model, transgenic mice were used for carcinogenesis and therapeutic vaccine studies (Doorbar, 2015;Eckert et al, 2000). Until recently, the only other PV associated with a mouse species was MmiPV1, which was isolated from a zoo colony of European harvest mice (Micromys minutus) (van Doorslaer et al, 2007;Sundberg et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…These include bovine PV (BPV1 and BPV2), cotton rabbit PV (CRPV), and canine PV (COPV and CfPV2), all of which have been used for vaccine and pathogenesis studies (Campo, 2002;Buitrago-Pérez et al, 2012). In the absence of a proper mouse HPV model, transgenic mice were used for carcinogenesis and therapeutic vaccine studies (Doorbar, 2015;Eckert et al, 2000). Until recently, the only other PV associated with a mouse species was MmiPV1, which was isolated from a zoo colony of European harvest mice (Micromys minutus) (van Doorslaer et al, 2007;Sundberg et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Although valuable research on HPV biology has emerged from in vitro systems or even human samples, a comprehensive understanding of disease progression has been hampered by the lack of appropriate animal models of HPV infection, since papillomavirus species-specificity prevents HPVs from infecting non-human species (Doorbar, 2016). Nevertheless, there are some animal PVs causing diseases in animal models that resemble the human situation.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is well stated that both HPV [9] and BPV promote DNA damages (mutations) that can lead to cancer initiation [10][11][12][13], there are few studies about the viral action in cell metabolism [5,[14][15][16]. This occurs due to the lack of attention given to in vitro models [17]. In this sense, since 2003, our group has demonstrated that primary cultures derived from BPV-infected lesions are useful model to understand the viral interaction with host chromatin [18].…”
Section: Introductionmentioning
confidence: 91%